2014
DOI: 10.1155/2014/246748
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q0 from Antrodia cinnamomea in Submerged Cultures Induces Reactive Oxygen Species‐Mediated Apoptosis in A549 Human Lung Cancer Cells

Abstract: We investigated the anticancer effects of Antrodia cinnamomea, a medicinal mushroom from Taiwan, on A549 human lung cancer cells using the ethyl acetate extract from submerged culture filtrates. Our results showed that 2,3-dimethoxy-5-methyl-1,4-benzoquinone (coenzyme Q0; CoQ0) derived from A. cinnamomea submerged culture filtrates has anticancer activity. CoQ0 treatment reduced the viability of A549, HepG2, and SW480 cancer cell lines. Furthermore, CoQ0 induced reactive oxygen species (ROS) generation and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…Owing to its potent anticancer/cytotoxic properties against human breast cancer 25 , and lung cancer cells 40 , we assume that CoQ 0 could be a potential candidate to treat human ovarian carcinoma cells. For the first time, we have demonstrated that CoQ 0 , isolated from Antrodia camphorata , potently killed the ovarian SKOV-3 cancer cells and induced cell-cycle arrest via decreased cell-cycle regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its potent anticancer/cytotoxic properties against human breast cancer 25 , and lung cancer cells 40 , we assume that CoQ 0 could be a potential candidate to treat human ovarian carcinoma cells. For the first time, we have demonstrated that CoQ 0 , isolated from Antrodia camphorata , potently killed the ovarian SKOV-3 cancer cells and induced cell-cycle arrest via decreased cell-cycle regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of CoQ 0 was associated with increased proportion of cells undergoing apoptosis, and this phenomenon was addressed by the induction of G 0 /G 1 cell-cycle arrest in MDA-MB-231 cells and S-phase arrest in SKBr3 cells 25 . CoQ 0 isolated from Antrodia cinnamomea submerged cultures has also reported to possess anticancer property by the decreased viability of A549, HepG2 and SW480 cancer cells, and increased ROS-mediated apoptosis 40 .…”
Section: Discussionmentioning
confidence: 99%
“…With the global increase in antibiotic resistance and safety concerns surrounding the use of chlorine-based disinfectants, the antibacterial properties of plant-derived compounds are increasingly being investigated [40,41]. CoQ 0 , derived from A. cinnamomea, has attracted attention for its potential as a natural food preservative and as a therapeutic antibiotic [28]. Based on growth curve analysis, we identi ed appropriate SICs of CoQ 0 that had no effect on growth for use in subsequent assays.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, the use of plant-derived compounds as alternative antimicrobials has gained signi cant attention as a result of increasing concerns over the safety of synthetic antimicrobial agents and the emergence of antibiotic-resistant bacteria [27]. Coenzyme Q 0 (CoQ 0 ; 2,3-dimethoxy-5-methyl-1,4benzoquinone; C 9 H 10 O 4 ) is a benzoquinone compound extracted from the fungus Antrodia camphorata [28]. It has demonstrated anti-tumor, anti-in ammatory, and anti-angiogenic properties [29], as well as antibacterial activity against Staphylococcus aureus and Listeria monocytogenes [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that treatment with anti-tumor agents from different categories induce free radicals in non-tumor cells in both in vitro and in vivo (Weijl et al, 1997). Extracts of A. cinnamomea or its derived compounds induce apoptosis in cancer cells through reactive oxygen species (ROS) gen- eration following DNA damage (Chung et al, 2014;Yang et al, 2013). Thus, prior to the in vitro assay, the cytotoxic effect of LACC on CHO-K1 cells was examined by MTT assay.…”
Section: Mammalian Chromosome Aberration Testmentioning
confidence: 99%